Silica-supported Nb(iii)–CH3 species can act as an efficient catalyst for the non-oxidative coupling of methane. (25th June 2021) - Lin, Xufeng; Ma, Lishuang; Zhao, Shidong; Xi, Yanyan; Shang, Hongyan; An, Gaojun; Lu, Changbo
Abstract : The Nb(iii )–CH3 catalyst lowers the energetic span of the whole catalytic cycle over its Ta and V analogues. Abstract : To upgrade methane to more valuable products, the non-oxidative coupling of methane (NOCM) is a hopeful method. This work investigates the mechanism and evaluates the feasibility of silica-supported single-site niobium (Nb) catalysts for NOCM by density functional theory (DFT) calculations. Two catalyst candidates were studied, namely, the silica-supported Nb(iii )–methyl catalyst (denoted as (SiO)2 Nb–CH3 ) and the silica-supported Nb(iii )–hydride catalyst (denoted as (SiO)2 Nb–H). The catalytic cycle working with (SiO)2 Nb–CH3 contains 5 elementary steps, and the one working with (SiO)2 Nb–H contains 6 elementary steps. (SiO)2 Nb–CH3 is much more effective in catalyzing NOCM than (SiO)2 Nb–H on the basis of the energetic span value. Interestingly, the silica-supported Nb(iii )–CH3 catalyst can have an increase of 2 orders of magnitude in the turnover frequency (TOF) for NOCM compared to the silica-supported Ta(iii )–CH3 catalyst, the latter having been experimentally used for NOCM catalysis. This work provides further insights into the mechanism of single-site metal catalysts for NOCM, and provides a direct guide for catalyst design for NOCM as well.